(untitled) (Interdisciplinary Research in Education, 2024)
Corruption is a major barrier to good governance and development worldwide. In Nepal, even after adopting federalism in 2015, corruption continues to weaken decentralized governance. This study examines its impact on federalism, with a focus on governance and education. It analyzes constitutional provisions, anti-corruption laws, and policy documents using qualitative research methods. The findings show that corruption appears in various forms, such as misuse of public funds, bribery, and political favoritism, all of which reduce transparency and accountability. Weak institutions and political interference further slow down the effective implementation of federalism. In the education sector, corruption affects policy execution, resource allocation, and institutional integrity, making quality education less accessible. To address these issues, the study recommends stricter anti-corruption laws, institutional reforms, and integrating civic education into school curricula. The success of federalism and good governance in Nepal depends on transparency, public participation, and independent oversight.